Meningkatkan Kepercayaan Diri Serta Minat Belajar Anak Dengan Motivasi dan Apresiasi di Panti Asuhan Karya Betzy - Lidia Enjela; Tuti Atika (Yayasan Literasi Sains Indonesia, 2022)
This study aims to increase children's self-confidence and interest in learning with motivation and appreciation. This research was conducted at the Karya Betzy Indonesia Foundation Orphanage. The subjects in this study were the children of the Karya Betzy Orphanage, totaling 43 children. This type of research is a qualitative research. The data collection technique in this research is observation. The data analysis technique used descriptive qualitative. The results of this research are in the form of a humanitarian project which is the topic of community service carried out at the Karya Betzy Indonesia Foundation Orphanage as a form of student service to provide knowledge that is beneficial to the surrounding community. Activities carried out include socialization, education, motivation and appreciation which will later change the mindset of the children who live in the Karya Betzy Indonesia Orphanage so that they can increase their self-confidence and motivation to learn so that they receive more knowledge. only in the orphanage or at school.